Titin I27: a protein with a complex folding landscape - Clarke, Jane (Henry Stewart Talks, 2007)
Examination of the folding of titin 127, Evolution of the protein to withstand stress from mutation, the environment and to withstand mechanical force in the muscle, Use of a combination of protein engineering, kinetic and thermodynamic measurements, computer simulations and single molecule atomic force microscopy to understand how evolution acts on protein sequences to allow them to adapt to stressful conditions, probably explaining why immunoglobulin-like proteins are used so successfully in evolution to perform a number of functions
Archived at 2016/04/17